SUBJECT OF LAW AS HOMO PRESENT - Meliakova, Yuliia; Kovalenko, Inna; Manuylov, Evgen; Kalnytskyi, Eduard (Revista Inclusiones, 2020)
The purpose of this research is a detailed analysis of the mode of a modern subject being in a number of parallel, consistent realities, consideration of its capabilities and development prospects. Special attention is paid to making an anthropological image of a post-human in the status of the subject of law, to justifying the relevance and effectiveness of his legal abilities in the modern simulation space. The scientific novelty of the results is an introduction to the field of philosophy of culture of the new concept of homo present (homo who is present), as well as its further substantiation as one of the conceptual characteristics of not only the subject of culture in principle, but, in particular, of the subject of law symbolizing the image of post-human as such. Thus, a man of post-non-classical culture manifests himself as a multidimensional co-participative polysubject. At the same time, the main mode of his being in these realities is presence, depriving the post-human of many abilities of a moral subject, but giving certain advantages to an actual subject, realizing in law. Thus, legal personality can be considered the main feature of the homo present, while legal reality can be considered the main reality of his presence and self-realization.